2001
DOI: 10.1093/ndt/16.8.1620
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of nut‐cracker phenomenon using renal Doppler ultrasound in orthostatic proteinuria

Abstract: NCP may be one of the leading causes of orthostatic proteinuria, and non-invasive renal Doppler US may be a useful diagnostic tool in the screening of NCP. In the future, the diagnostic criteria of NCP must be redefined in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
55
0
3

Year Published

2003
2003
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(59 citation statements)
references
References 18 publications
1
55
0
3
Order By: Relevance
“…The sonographic diagnostic criterion consists of a peak flow velocity ratio between the AMP and hilar portion of the LRV of greater than 5. 40,41 Investigations regarding the use of noninvasive sonographic imaging for the confirmation of the nutcracker phenomenon in children and adults have been performed previously. 10,11,[42][43][44] The scope of this study focused on quantitative description and hemodynamic evaluation of the LRV and on the presence of the nutcracker phenomenon (compression of the LRV between the aorta and superior mesenteric artery) 1,[4][5][6][7][9][10] to establish auxiliary diagnostic leads in the determination of the cause of varicocele using noninvasive sonography.…”
mentioning
confidence: 99%
“…The sonographic diagnostic criterion consists of a peak flow velocity ratio between the AMP and hilar portion of the LRV of greater than 5. 40,41 Investigations regarding the use of noninvasive sonographic imaging for the confirmation of the nutcracker phenomenon in children and adults have been performed previously. 10,11,[42][43][44] The scope of this study focused on quantitative description and hemodynamic evaluation of the LRV and on the presence of the nutcracker phenomenon (compression of the LRV between the aorta and superior mesenteric artery) 1,[4][5][6][7][9][10] to establish auxiliary diagnostic leads in the determination of the cause of varicocele using noninvasive sonography.…”
mentioning
confidence: 99%
“…15 For diagnosing pediatric patients, we prefer to use the combined cutoff level as described above 5 because this approach has been used to diagnose children in previous studies and has the highest reported sensitivity and specificity. 5,8 Our patient experienced a sudden onset of gross hematuria, without proteinuria, after exercise. Causes of hematuria other than NCP, such as infection, urolithiasis, and glomerulonephritis, were excluded by the clinical and laboratory findings.…”
Section: Discussionmentioning
confidence: 87%
“…Conservative treatment is adequate if the symptoms are mild, but in cases of massive hematuria and abdominal and flank pain, which are probably caused by ureteral passage of blood clots, surgical intervention is indicated. 2 The hematuria accompanying NCP is sometimes associated with proteinuria [7][8][9] and may result from increased pressure on the LRV, causing microruptures of thin-walled veins into the renal collecting system or the caliceal fornix or communication between dilated venous sinuses and adjacent renal calyces. 8,10 Because the hematuria caused by NCP is nonglomerular, erythrocytes in the urine are isomorphic on phase-contrast microscopic examination.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations